Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1995
DOI: 10.1093/jn/125.9.2348
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Solubility, Intestinal Sojourn Time and Paracellular Permeability Codetermine Passive Calcium Absorption in Rats

Abstract: To investigate the nonsaturable, paracellular pathway of intestinal Ca absorption, the luminal contents of 12-cm segments of the intestine of 8-wk-old male Sprague-Dawley rats were analyzed for pH, sojourn time and soluble and insoluble Ca over a 24-h period. The rats had been fed one of two high Ca diets for 2 wk: 1.5% Ca (diet group 3a) and 3.1% (diet group 5a). The pH of the small intestine increased from < 6.6 to > 8.0 from duodenum to ileum; transit time increased from 2.5 min in the duodenum to 58 min in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
58
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 89 publications
(62 citation statements)
references
References 9 publications
4
58
0
Order By: Relevance
“…2). These results agree with the findings of the in vitro experiments with isolated mucosa of the small intestinal, 7,10) and are concrete and direct evidence for enhancement of Ca absorption by DFAs in the small intestine.…”
Section: =ð12-polyethylene Glycol/calcium In Infused Solutionþsupporting
confidence: 91%
See 1 more Smart Citation
“…2). These results agree with the findings of the in vitro experiments with isolated mucosa of the small intestinal, 7,10) and are concrete and direct evidence for enhancement of Ca absorption by DFAs in the small intestine.…”
Section: =ð12-polyethylene Glycol/calcium In Infused Solutionþsupporting
confidence: 91%
“…Previously, we found that DFAIII promotes Ca absorption by activating the paracellular transport pathway through tight junction. 10) It has been reported that transit speed in the small intestine is an important factor for determination of diffusional Ca transport via the paracellular pathway, especially at high Ca levels in the diet. 11) We used a perfusion medium with a high but physiological Ca concentration, 10 mmol/l, 12) much higher than the Kt of active Ca transport, 0.32 mmol/l, in the duodenum.…”
Section: =ð12-polyethylene Glycol/calcium In Infused Solutionþmentioning
confidence: 99%
“…Although intestinal Ca 2ϩ absorption has been studied extensively, reliable data on the ionized Ca 2ϩ concentrations along the small intestines is lacking (28). It is noteworthy that ionized Ca 2ϩ concentrations in the gut are largely determined by luminal pH and insoluble complex formation, which becomes more significant at the more alkaline pH of the lower intestines, where trypsin degradation was shown to occur (29).…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this is the activation of the Na + /H + exchanger by a lower Na + concentration, as demonstrated with the aid of inhibitor studies [20]. It is unlikely that the drop in pH caused transcellular calcium transport, inasmuch as addition of mannitol or other polyols [15,28] to jejunal loops which are more acidic (pH < 6.6) [11] had no effect on transcellular calcium transport.…”
Section: Discussionmentioning
confidence: 99%
“…In the absence of calbindin D 9k , self-diffusion of the calcium ion is so slow that the transcellular component is essentially nil and absorption is only mediated by the paracellular process, dominant in both jejunum and ileum. However, because the time spent by chyme in the ileum accounts for three-fourths of the 3 h that the chyme sojourns in the small intestine, the ileum is the principal site of calcium absorption [11,25].…”
Section: Introductionmentioning
confidence: 99%